Modernization in the Education System of Nepal: Reflections from School Education Sector Plan - Joshi, Tap Raj (Nepalese Journal of Society and Culture, 2025)
The terms ‘modernization’ and ‘education’ are intertwined. These terms maintain a reciprocal relationship that complements each other, allowing them to grow and contribute to the nation-state’s development. The modernization of any state has a significant impact on its education system. The study aims to explore how the process of modernization has shaped the current education system of Nepal and how the elements of modernization have been incorporated into the School Education Sector Plan (SESP) 2022/23–2031/32. It analyzes the SESP document which outlines the educational plans and policies of Nepal. Simultaneously, the study investigates how these plans and policies contribute to the modernization of the education system. Relevant literatures from books and journals were reviewed to examine the relationship between education and modernization. A qualitative document analysis method was employed to critically analyze the elements of modernization embedded in the objectives, strategies and guidelines of the SESP document. This study reveals that SESP aims to promote equity, inclusivity, digital learning, Technical and Vocational Education and Training (TEVT), the use of Information and Communication Technology (ICT), along with the protection of child rights and healthcare to increase access and ensure quality learning. Additionally, it encourages community participation, implementation of decentralization policy and use of the Integrated Educational Management Information System (IEMIS) in schools to ensure good educational governance and a better school system.